A puzzling Cretaceous psyllid-type forewing from the South of China - Hakim, Marina; Huang, Di-Ying (Zootaxa, 2024)
The new taxon Fujianella paradoxa gen. et sp. nov. is described and illustrated from the Early Cretaceous Bantou Formation, in Yong’an County, Fujian Province, southeastern China. It is placed in the insect suborder Sternorrhyncha (Hemiptera) but left unassigned to any family at present due to its controversial features. This fossil record represents the second psyllid-looking taxon reported from the Cretaceous of China, found mainly in the Jurassic. This discovery further showcases the similarities in entomofauna between the Middle Jurassic Yanliao biota in the North of China and the Early Cretaceous in the South of China.